Radiomics-Based Texture Analysis of 68Ga-DOTATATE Positron Emission Tomography and Computed Tomography Images as a Prognostic Biomarker in Adults With Neuroendocrine Cancers Treated With 177Lu-DOTATATE - Atkinson, Charlotte; Ganeshan, Balaji; Endozo, Raymond; Wan, Simon; Aldridge, Matthew D.; Groves, Ashley M.; Bomanji, Jamshed B.; Gaze, Mark N. (Frontiers in Oncology, 2021)
Purpose Neuroendocrine tumours (NET) are rare cancers with variable behavior. A better understanding of prognosis would aid individualised management. The aim of this hypothesis-generating pilot study was to investigate the prognostic potential of tumour heterogeneity and tracer avidity in NET using texture analysis (TA) of 68Ga-DOTATATE positron emission tomography (PET) and non-enhanced computed tomography (CT) performed at baseline in patients treated with 177Lu-DOTATATE. It aims to justify a larger scale study to evaluate its clinical value. Methods The pretherapy 68Ga-DOTATATE PET-CT scans of 44 patients with metastatic NET (carcinoid, pancreatic, thyroid, head and neck, catecholamine secreting and unknown primary NET) treated with 177Lu-DOTATATE were analysed retrospectively using commercially available texture analysis research software. Image filtration extracted and enhanced objects of different sizes (fine, medium, coarse), then quantified heterogeneity by statistical and histogram based parameters (mean intensity, standard-deviation, entropy, mean of positive pixels, skewness and kurtosis). Regions of interest were manually drawn around up to five of the most 68Ga-DOTATATE avid lesions for each patient. 68Gallium uptake on PET was quantified as SUVmax and SUVmean. Associations between imaging and clinical markers with progression-free (PFS) and overall survival (OS) were assessed using univariate Kaplan-Meier analysis. Independence of the significant univariate markers of survival was tested using multivariate Cox regression analysis. Results Measures of heterogeneity (higher kurtosis, higher entropy and lower skewness) on coarse texture scale CT and unfiltered PET images predicted shorter PFS (CT coarse kurtosis: p=0.05, PET entropy: p=0.01, PET skewness: p=0.03) and shorter OS (CT coarse kurtosis: p=0.05, PET entropy: p=0.01, PET skewness p=0.02). Conventional PET parameters such as SUVmax and SUVmean showed trends towards predicting outcome but were not statistically significant. Multivariate analysis identified that CT TA (coarse kurtosis: HR=2.57, 95%CI=1.22-5.38, p=0.013) independently predicted PFS and PET TA (unfiltered skewness: HR=9.05, 95%CI=1.19-68.91, p=0.033) independently predicted OS. Conclusion These preliminary data generate a hypothesis that radiomic analysis of neuroendocrine cancer on 68Ga-DOTATATE PET-CT may be of prognostic value and a valuable addition to the assessment of patients .